Toxicity of silver nanoparticles and silver nitrate on Nassarius reticulatus larvae - Khodaparast, Zahra (2016)
Production and utilization of silver nanoparticles (AgNPs) for various applications is growing rapidly, mainly due to their antibacterial activity. Their inclusion in many consumer products led to an increased release of AgNPs in the environment, especially in aquatic ecosystems. AgNPs reach both freshwater and marine environments from the effluents of the wastewater treatment plants, presenting differentiated behavior in these two environments potentially influencing its toxicity. The study of AgNPs toxicity to marine organisms is extremely important to the assessment of the potential risk of AgNPs in the environment. The toxicity of AgNPs on the living organisms is dependent on various environmental conditions. Regarding the toxicity of AgNPs in the marine environment, there is a lack of information on the toxic effects at different salinities. This study upsurges to fill this gap, being the first report on the effects of AgNPs on marine gastropods, using Nassarius reticulatus as a case study. N. reticulatus adults were collected from a reference population in Ria de Aveiro (NW Portugal, 40° 38' 33.24"N | 8° 44' 06.69’’W). Specimens were transported to the laboratory in local seawater and kept in aquaria to spawn. Egg capsules were maintained until veliger larva were noticed, which enclosure was induced by cesarean. These recently hatched larvae were then exposed to nominal concentrations of AgNPs and Ag+ (0.1, 1, 10, 100 μg Ag/L) for up to 96 h, either in the presence or absence of food. Larval mortality and swimming behavior –namely the velum beating arrest–were determined for each treatment. The median lethal concentration (LC50) of AgNPs was higher to that of ionic Ag (AgNO3). Results also revealed that the negative impact of AgNPs on N. reticulatus veligers swimming ability is higher when compared with the effect of ionic Ag (EC50-96 h 1.044 μg Ag/L). However, although the velum arrests have significantly decreased under Ag+ exposure, AgNPs did not show any effects. Additionally, the presence of the food proved to be an effective factor that can cause a significant drop in the mortality of the N. reticulatus larvae exposed to AgNPs.